The Use of Information and Communication Technology in Mathematics Education: Does Gender Make a Difference? - Yuberta, Fauzi; firmanti, Pipit (Continuous Education: Journal of Science and Research, 2024)
Gender equality is a global trend that is a matter for discussion, including in mathematics learning. The ability to use gender-based technology is fundamental to improving the quality of learning. This research aims to describe differences in ICT use strategies by mathematics teachers and differences in students' technology use skills based on gender in mathematics learning. This research is qualitative research with a literature study approach. The indicators for mathematics teachers are viewed from the aspects of the teacher's level of knowledge of ICT, use of technology per hour per day and attitude. Meanwhile, the differences in the ability of male and female students to utilize ICT in learning mathematics can be noticed from the aspects of perception, students' experience and attitudes. The results of the discussion show that mathematics teachers in Indonesia tend to use technology not constructively or only as a learning tool. Female teachers have better strategies or approaches to teaching the integration of technology in mathematics learning while male teachers are more proficient in using or operating digital tools. On the other hand, male students' skills in using technology are better than female students. However, female students can also have the same abilities as males if they have a positive view of integrating technology into mathematics learning.